Geothermal energy for sustainable water resources management. Issue 1 (2nd January 2020) - Chandrasekharam, D.; Lashin, A.; Al Arifi, Nassir; Al-Bassam, Abdulaziz M.; Chandrasekhar, Varun
ABSTRACT: With ever-increasing population and steep declining freshwater supply, the future concern of MENA and Sub-Saharan countries is food security. Egypt is more vulnerable to food security due to the increased water rights being exercised by the countries sharing the Nile River. Assuming that Egypt by 2025 will achieve 1000 m 3 /y per capita consumption of water, with the population growing beyond 109 millions, the water available by 2025 would be around 106 billion m 3 /y. With increasing pressure from the Nile River basin riparian countries, Egypt may not be able to manage with the current 58 billion m 3 of water from the Aswan dam to achieve per capita goal. To maintain the current per capita water consumption of 636 m 3 /y Egypt may need about 1200 desalination plants and 200 × 10 6 kWh electricity is required to operate these plants and the CO2 emissions due to this process will be around 80–160 million tones. Electricity generated from hydrothermal sources can supply 659 × 10 9 m 3 /year of desalinated water while the EGS can generate 58, 400 × 10 9 m 3 /y of desalinated water from the Red Sea. This will help the country to meet the current fresh water deficit of 48 × 10 9 m 3 /y. By the year 2025, the demand for fresh water will be of the order of 106 × 10 9 m 3 /y to maintain 1000 m 3 /y per capita water consumption. Egypt can set an example to MENA and Sub-Saharan countries by using geothermal energy for sustainable development and future water and food security.